2021
DOI: 10.1016/j.heliyon.2021.e06516
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling and multi-objective optimization of engine performance of biodiesel made with castor oil

Abstract: In this research the engine performance of biodiesel made with castor oil through homogeneous alkali catalyzed transesterification was analyzed. The input variables for the performance analysis were biodiesel blend and engine speed while the response variables were break power (BP), basic specific fuel consumption (BSFC), break thermal efficiency (BTE), torque and unit cost. The engine performance was modeled using artificial neural network (ANN) and the ANN was subsequently used as the objective function for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As the rotational speed increases, the power generated by each fuel unit decreases, and the BSFC of all five experimental fuels shows an increasing trend. Muteeb ul Haq et al [40] and Jonah Chukwudi Umeuzuegbu et al [41] also found the same trend in BSFC variation when studying castor biodiesel blends.…”
Section: Brake Specific Fuel Consumption (Bsfc)mentioning
confidence: 68%
“…As the rotational speed increases, the power generated by each fuel unit decreases, and the BSFC of all five experimental fuels shows an increasing trend. Muteeb ul Haq et al [40] and Jonah Chukwudi Umeuzuegbu et al [41] also found the same trend in BSFC variation when studying castor biodiesel blends.…”
Section: Brake Specific Fuel Consumption (Bsfc)mentioning
confidence: 68%
“…To avoid financial constraints and time-consuming experiments, scholars have employed different modeling techniques, including artificial intelligence (AI), in terms of an artificial neural network (ANN) tool, and fuzzy modeling in modeling engine performances and exhaust emissions [41][42][43][44]. Accordingly, the correlation coefficient between the experimental data and ANN predictions can accurately forecast the engine efficiency and exhaust emissions powered with biodiesel mixes [45].…”
Section: Literature Review On Engine Performance Optimization Approachesmentioning
confidence: 99%
“…In the literature, numerous research studies can be found which try to address the application of CPA in developing computational methods for production and logistics systems [13,6,7,4,12]. Furthermore, most studies have been addressing sustainable development as a necessity for real-life problems to be achieved through intelligent methods [3].…”
Section: Published Researchmentioning
confidence: 99%